2018
DOI: 10.1001/jamapediatrics.2018.1792
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Temporal Changes in Neonatal Mortality and Spontaneous and Clinician-Initiated Deliveries in the United States, 2006-2013

Abstract: IMPORTANCE Preterm and postterm deliveries have declined since 2005 in the United States, but the association between these changes and neonatal mortality remains unknown. OBJECTIVE To estimate changes in the gestational age distribution among spontaneous and clinician-initiated deliveries between 2006 and 2013 and associated changes in neonatal mortality. DESIGN, SETTING, AND PARTICIPANTS A retrospective cohort analysis was conducted of 22 million singleton live births without major malformations in the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…In the United States, neonatal survival (during the first 28 days) among singleton live births at 20-27 weeks' gestational age without malformations increased from 37% in 2006 to 50% in 2013. 28 In parallel, rates of stillbirths increased. 29 The present study showed a survival rate of 77% among all live-born infants at 22-26 weeks' gestational age in 2014-2016, and the stillbirth rate was found to be significantly lower than the rate reported in the rest of Europe.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, neonatal survival (during the first 28 days) among singleton live births at 20-27 weeks' gestational age without malformations increased from 37% in 2006 to 50% in 2013. 28 In parallel, rates of stillbirths increased. 29 The present study showed a survival rate of 77% among all live-born infants at 22-26 weeks' gestational age in 2014-2016, and the stillbirth rate was found to be significantly lower than the rate reported in the rest of Europe.…”
Section: Discussionmentioning
confidence: 99%
“…For preterm birth, this question is somewhat more complex as indicated earlier delivery is a strategy used to reduce risks of stillbirth or other adverse perinatal outcomes associated with maternal age. In the US, clinician‐indicated deliveries represent 41% of all preterm births . Kaiser et al find that clinician‐indicated births are responsible for the increase in risk of preterm birth associated with older maternal age.…”
mentioning
confidence: 99%
“…In the US, clinician-indicated deliveries represent 41% of all preterm births. 10 Kaiser et al find that clinician-indicated births are responsible for the increase in risk of preterm birth associated with older maternal age.…”
mentioning
confidence: 99%
“…Fully saturated models were developed to evaluate whether percentage change across HRR and demographics were statistically significant using generalized estimation equations with normal distributions and identity linkage. 23 Quantile regression models were used to calculate the difference and 95% confidence interval (CI) of median travel distance between the years 2000 and 2014 to test whether the median travel distance was statistically different between the years.…”
Section: New York State Hrrs Stratified By Population Densitymentioning
confidence: 99%